Leaf anatomy changes related to cultivate in vivo and in vitro and during pre-acclimatization of Crambe abyssinica Hochst - Terra Werner, Elias; Rozindo Dias Milanez, Camilla; Barcelos Passos Lima Gontijo, Andreia; Bastos Soares, Taís Cristina; Teixeira do Amaral, José Augusto (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2023)
This study aimed to characterize and evaluate possible modifications in the leaf anatomy of crambe in the in vivo and in vitro environment and during pre-acclimatization. The results from the comparison of leaves in vivo, in vitro and during pre-acclimatization indicated that there was no statistical difference with regards to blade, mesophyll, palisade and spongy parenchyma, and midrib. Significant difference existed in the thickness adaxial and abaxial epidermal surfaces, with the highest values being observed for in vivo conditions. The area of the vascular bundle was superior and significantly different under in vitro conditions. Therefore, the alterations observed in the structure and thickness of the leaves in the pre-acclimatization treatments hampered the process of plantlet establishment ex vitro.